Suicide Ideation Prevention Among University Students Through the Workshop: "I’ve Given Up!! What Should I Do??" - Meirendra, Rizqiariq Arrofiq; Cahyati, Ma'rifatullillah Destiana; Martin , Ricky Alejandro; Ramadhani , Fitriani Rahma; Pertiwi , Fanny Anggraini Jati (Psikologi Prima, 2025)
WHO notes that Indonesia ranks eighth among ASEAN countries with high suicide rates. Increased suicidal ideation among students is a serious issue that requires immediate action. This study aims to evaluate the effectiveness of the "I have Grown Up! What Should I Do?" workshop in reducing the level of suicidal ideation in college students. The study employed a pre-experimental design with a one-group pretest-posttest approach. The research subjects consisted of 75 students in Surabaya, selected through a purposive sampling technique. Data were collected using the survey method with instruments Revised-Suicide Ideation Scale (R-SIS). Data analysis was conducted using a paired sample t-test. The analysis showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. This finding proves that the workshop "I have Grown Up! What Should I Do?" workshop is effective in reducing the tendency of suicidal ideation in college students.